Temporomandibular joint prosthesis as treatment option for mandibular condyle fractures: a systematic review and meta-analysis. Issue 1 (January 2023) - Niezen, E.T.; van Minnen, B.; Bos, R.R.M.; Dijkstra, P.U.
Abstract: The aim of this study was to perform a systematic review of the literature on the temporomandibular joint (TMJ) prosthesis as a treatment option after mandibular condyle fracture. Three databases were searched (PubMed, Embase, Cochrane Library) and 2670 unique papers were identified. A total of 337 studies were included (121 case reports, 89 case series, and 127 cohort/clinical studies). In total 14, 396 patients and 21, 560 prostheses were described. Of the 127 cohort or clinical studies, 100 (79%) reported inclusion criteria, 54 (43%) reported exclusion criteria, and 96 (76%) reported the inclusion period. The base population from which patients were recruited was reported in 57 studies (45%). The reason for TMJ prosthesis implantation was reported for 4177 patients (29.0%). A history of condylar fracture was present in 83 patients (2.0%); a history of mandibular trauma was present in 580 patients (13.9%). The meta-analysis showed a pooled prevalence of condylar fracture of 1.6% (95% confidence interval 0.9–2.4%) and a pooled prevalence of trauma or condylar fracture of 11.3% (95% confidence interval 7.1–16.0%). Heterogeneity was highly significant ( P < 0.001). The TMJ prosthesis appears to be reserved for patients with persistent pain, bony or fibrous ankylosis, or osteomyelitis after primary closed or open treatment of fractures of the mandibular condyle.